2012
DOI: 10.1007/s00216-012-5972-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recombinant human EPO administered to horses using MAIIA lateral flow isoform test

Abstract: Doping of horses with recombinant human erythropoietin (rHuEPO) to illegally enhance their endurance capacity in horseracing has been reported during the last years. This leads to increased blood viscosity which can result in sudden death and is of concern for the horse welfare. Additionally, the horse can start production of rHuEPO antibodies, which cross-reacts with endogenous equine EPO and can lead to severe anaemia and even death. In this study, a novel micro-chromatographic method, EPO WGA MAIIA, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…Three of the subjects will be positive for doping (10,11,13) being outside the 99.99% CL. Three of the subjects might be suspected for doping (9,12,15) being outside the 99% CL, while only two subjects are negative (25%). The haemoglobin and haematocrit values exceed the limits for competition exclusion only for one subject (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the subjects will be positive for doping (10,11,13) being outside the 99.99% CL. Three of the subjects might be suspected for doping (9,12,15) being outside the 99% CL, while only two subjects are negative (25%). The haemoglobin and haematocrit values exceed the limits for competition exclusion only for one subject (13).…”
Section: Discussionmentioning
confidence: 99%
“…The EPO WGA MAIIA method has previously proven to be successful in the detection of several isoforms of EPO [11] like epoetin alpha, omega, delta, darbepoetin alpha and CERA. The method has also successfully been identifying identified the injection of epoetin-alpha and darbepoetin alpha in horses [15].…”
Section: Detection Of Different Types Of Rhepomentioning
confidence: 99%
See 1 more Smart Citation
“…A study measuring the interaction between EPO carbohydrate structures and lectins found that the lectin wheat germ agglutinin was especially useful for distinguishing recombinant and endogenous EPO [19]. The interaction between EPO and WGA has been used in a rapid lateral flow test for identification of rhEPO doping in humans and in horses [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A rhEPO também pode ser determinada pela cromatografia liquida acoplada a espectrometria de massa (LC-MS/MS) (Scarth et al 2011). Mais recentemente, o método de micro-cromatografia WGA MAIIA foi desenvolvido para detecção de agentes estimulantes da eritropoiese na urina e plasma de equinos (Lönnberg et al 2012).…”
Section: Resultsunclassified